An experimental study on the cyclic behaviour of riveted stiffened seat angle connection with concrete encasement. - Bisson, Marc A. (University of Ottawa (Canada), 1997)
Many older buildings have been constructed using what are considered today as semi-rigid or flexible types of connections. A concrete encasement was typically added to columns in the past for the sole purpose of fire protection. The behaviour of semi-rigid connections under cyclic loading and the contribution to seismic resistance of the concrete encasement is a concern. An experimental investigation was undertaken to determine the effect of concrete encasement on cyclic behaviour of a typical riveted stiffened seat angle connection, and the improvement in behaviour when retrofitted with a proposed method. Existing connections were tested and hysteretic moment-rotation curves were obtained. Models previously developed by other researchers were verified and practical recommendations are presented.
Keywords: Engineering, Civil.